Revisiting the Taxonomy of Ophiorrhiza brunonis var. johnsonii (Rubiaceae), a Little-Known Endemic Species of the Western Ghats, India - Filimban, Faten Zubair; Kumar, Ettickal Sukumaran Santhosh (Phytotaxa, 2026)
The taxonomy and nomenclature of Ophiorrhiza brunonis var. johnsonii are revisited. It is recognized here as a distinct species, viz. O. johnsonii (Hook.f.) E.S.S. Kumar & Faten comb. et stat. nov. The detailed comparative morphology with its associated taxa is discussed in the present article, along with updated nomenclature.